CATEGORICAL ANALYSIS OF STUDENT ENTHUSIASM RELATED TO THE 2024 INDONESIAN ELECTION WITH CHI-SQUARE INDEPENDENCE TEST - Ilham Darussalam; Evi WIjayawati; M. Syahrie Khamdani; Fitriana Nur Afifa (Parameter: Journal of Statistics, 2025)
General elections in Indonesia are crucial for democracy, enabling citizens to directly choose their leaders. But the abstention or the "whites" in Indonesian elections is growing due to perceived political bias in the state apparatus operating under bureaucratic democracy principles. KPU RI has designated the National Permanent Voter List for the 2024 election, with 52% being young voters consisting of students. Ranging in age from 17 to 22 years old, the students will make a major contribution to the number of votes and the number of abstinences. In this study, a chi-square independence test was conducted to analyze the factors that are thought to influence student enthusiasm regarding the 2024 Indonesian elections. The results of this study indicate that social media intensity has a significant effect on student enthusiasm regarding the 2024 Indonesian elections, while gender and regional origin have no significant effect.